The role of marine protected areas in enhancing coral cover and reef fish communities - Z.A. Harahap; D.G. Bengen; I.W. Nurjaya; S.B. Agus; Y. Naulita; R.M. Siringoringo (Global Journal of Environmental Science and Management, 2025)
BACKGROUND AND OBJECTIVES: Coral reefs are vital ecosystems that support a diverse array of marine species and provide essential services such as coastal protection, fisheries, and tourism. However, anthropogenic pressures increasingly threaten these ecosystems, including overfishing, pollution, and climate change. Marine protected areas, especially no-take zones, have emerged as practical tools for safeguarding coral reefs and enhancing biodiversity. The study objectives were to evaluates the role of no-take zones in promoting coral cover, reducing coral degradation, and supporting the diversity and abundance of reef fish communities in the Tapanuli Tengah Marine Conservation area, North Sumatra, Indonesia.METHODS: Field surveys were conducted in three no-take zones and adjacent non-protected areas. Coral cover was assessed using the underwater photo transect  method, while reef fish communities were surveyed using the underwater visual census technique. Data were analyzed to compare coral health, fish abundance, and species diversity between protected and non-protected zones. Statistical analyses were used to evaluate correlations between coral cover and fish communities and the effectiveness of no-take zones in supporting biodiversity.FINDINGS: Results revealed significantly higher hard coral cover and lower macroalgal growth in no-take zones than in non-protected areas. Fish species richness and abundance were also substantially more significant in no-take zones. Key reef fish families such as Pomacentridae, Apogonidae, and Caesionidae were closely associated with healthy coral habitats, whereas algae-covered substrates and disturbance-tolerant species such as Acanthuridae and Lethrinidae dominated degraded zones.CONCLUSION: This study highlights the effectiveness of no-take zones in improving coral reef health and enhancing reef fish biodiversity. The findings support expanding and strictly enforcing no-take zones to mitigate the impacts of overfishing and environmental degradation. Continued research is recommended to evaluate site-specific drivers and long-term ecological outcomes to ensure sustainable benefits for marine ecosystems and coastal communities.